Chemical characteristics of the Bandaiko hyper-acidic hot spring in Kusatsu Town, Gunma prefecture, and evaluation test of scale for binary power generation - Mio Ichino; Toshio Inoue; Yuka Kubotsu; Hideo Takizawa; Yukiko Hoshino; Daisuke Tanaka; Akira Ueda; Hideki Kuramitz (Geothermics, 2027)

Environmental impact assessment of seal water systems during construction of rock cavern tanks at the Namikata National LPG stockpiling base: Characterization of scale deposition using scale surveys and column flow tests - SeungYoul Yoo; Akira Ueda; Akiko Ozawa; Yasushi Kusakabe; Minenari Hiroki; Masahiro Ohkawa; Shinichi Tanikawa (Applied Geochemistry, 2026)

Differences in vegetation types, seasonal and temporal changes in the frequency of occurrence of vertebrate species that contribute to the decomposition of sika deer carcasses - Junco Nagata; Shin-Ichi Horino; Masahiro Sueyoshi; Akira Ueda; Hayato Iijima (European Journal of Wildlife Research, 2026)

Deep learning approach for classifying grazing behavior in yearling horses using triaxial accelerometer data: A pilot study - Uta Kamiya; Kasumi Kakiuchi; Kensuke Kawamura; Koichiro Ueda; Masahito Kawai; Akira Matsui; Natsuko Negishi (Journal of Equine Veterinary Science, 2025)

Interactions between basalt and CO2-saturated water at varying temperatures (100°C–300 °C) in a duplex reactor - Heejun Yang; Akira Ueda; Hideki Kuramitz; Amane Terai (Applied Geochemistry, 2025)

Tree retention for conserving saproxylic beetles in harvested conifer plantations - Satoshi Yamanaka; Akira Ueda; Naoyuki Furuya; Takuya Kobayashi; Hideaki Goto; Kenichi Ozaki (Forest Ecology and Management, 2025)

Scale evaluation in geothermal fluids by a batch-type method using fiber optic scale sensor - Sakurako Satake; Ai Hosoki; Airi Suka; Yukiko Hoshino; Heejun Yang; Akira Ueda; Hideki Kuramitz; Amane Terai (Geothermics, 2025)

Development of a novel in-sediment passive sampler for profiling orthophosphate and internal phosphorus release near the sediment–water interface in a eutrophic lake - Kazuto Sano; Jumpei Ueda; Akira Hafuka; Katsuki Kimura (Water Research, 2025)

Isotope geochemical study of the origin and formation mechanism of carbonate minerals in geothermal wells and surrounding hot spring waters in the western Unzen area - Akira Ueda; Heejun Yang; Yukiko Hoshino; Sakurako Satake; Dongyang Mao; Amane Terai (Applied Geochemistry, 2025)

Seasonal timing of ecosystem linkage mediates life‐history variation in a salmonid fish population - Rui Ueda; Minoru Kanaiwa; Akira Terui; Gaku Takimoto; Takuya Sato (Ecology, 2025)
Life‐history variation can contribute to the long‐term persistence of populations; however, it remains unclear which environmental factors drive life‐history variation within a population. Seasonally recurring resource subsidies are common in nature and may influence variations in recipient consumers' life‐history traits. In this study, we experimentally demonstrated that terrestrial invertebrate subsidies occurring early in the growing season facilitated consumer individuals to adopt fast growth. In contrast, fewer consumer individuals adopted fast growth when subsidies occurred late in the growing season. Consumer individuals that adopted fast growth matured early at age 1, suggesting that the observed variation in life history emerged along with a fast–slow life‐history continuum. The estimated survival probability was lower in consumer individuals from the faster growth cluster in the no‐supply treatment (control), suggesting a growth–survival trade‐off. However, the growth–survival trade‐off became unclear in the early‐supply treatment and even reversed in the late‐supply treatment. As a result, the frequency of consumer individuals maturing at age 1 was higher in the early‐supply treatment than in the late‐supply treatment and no‐supply treatment, implying a higher short‐term population growth with the early subsidies. Our findings highlight that seasonal ecosystem linkages through resource subsidies help us understand how life‐history variation can be maintained within a population at the landscape scale.

Geochemical study of fluid origin and caprock formation with carbonate mineral precipitation in the Okuaizu geothermal area - Dongyang Mao; Jing Zhang; Yukiko Hoshino; Sakurako Satake; Heejun Yang; Hideki Kuramitz; Akira Ueda; Amane Terai (Geothermics, 2025)

Isotope geochemical study of carbonate formation in the 84N-3t well in the Oku-Aizu geothermal area: Natural analog study of fluid origin during caprock formation - Dongyang Mao; Jing Zhang; Akira Ueda; Yukiko Hoshino; Ryosuke Oochi; Kensuke Matsumoto; Hisae Kaneko; Amane Terai (Geothermics, 2024)

Retention forestry in plantations: Synthesizing key findings of early studies from a long-term experiment in northern Japan - Kenichi Ozaki; Nobuhiro Akashi; Kazuhiro Kawamura; Keisuke Obase; Akira Ueda; Akira Unno; Satoshi Yamanaka; Yuichi Yamaura (Forest Ecology and Management, 2024)

Competitive exclusion of a burying beetle by mongoose - Akira Ueda (Biological Invasions, 2024)

Innovative receiving phase for Chemcatcher® passive sampler for phosphorus in the water environment: Calibration of sampling rate by water temperature and pH - Akira Hafuka; Yuma Okuda; Kazuto Sano; Jumpei Ueda; Katsuki Kimura (Water Research, 2023)

Comprehensive analyses of plant hormones in etiolated pea and maize seedlings grown under microgravity conditions in space: Relevance to the International Space Station experiment “Auxin Transport” - Chiaki Yamazaki; Tomokazu Yamazaki; Mikiko Kojima; Yumiko Takebayashi; Hitoshi Sakakibara; Eiji Uheda; Mariko Oka; Motoshi Kamada; Toru Shimazu; Haruo Kasahara; Hiromi Sano; Tomomi Suzuki; et al. (Life Sciences in Space Research, 2023)

Effects of dispersed and aggregated retention-cuttings and differently sized clear-cuttings in conifer plantations on necrophagous silphid and dung beetle assemblages - Akira Ueda; Hiroki Itô; Shigeho Sato (Journal of Insect Conservation, 2022)

A novel challenge of nondestructive analysis on OGATA Koan’s sealed medicine by muonic X-ray analysis - Kayoko Shimada-Takaura; Kazuhiko Ninomiya; Akira Sato; Naomi Ueda; Motonobu Tampo; Soshi Takeshita; Izumi Umegaki; Yasuhiro Miyake; Kyoko Takahashi (Journal of Natural Medicines, 2021)

The basement geology of Japan from A to Z - Simon R. Wallis; Ken Yamaoka; Hiroshi Mori; Akira Ishiwatari; Kazuhiro Miyazaki; Hayato Ueda (Island Arc, 2020)
The Precambrian and lower Paleozoic units of the Japanese basement such as the Hida Oki and South Kitakami terranes have geological affinities with the eastern Asia continent and particularly strong correlation with units of the South China block. There are also indications from units such as the Hitachi metamorphics of the Abukuma terrane and blocks in the Maizuru terrane that some material may have been derived from the North China block. In addition to magmatism, the Japanese region has seen substantial growth due to tectonic accretion. The accreted units dominantly consist of mudstone and sandstone derived from the continental margin with lesser amounts of basaltic rocks associated with siliceous deep ocean sediments and local limestone. Two main phases of accretionary activity and related metamorphism are recorded in the Jurassic Mino–Tanba–Ashio, Chichibu, and North Kitakami terranes and in the Cretaceous to Neogene Shimanto and Sanbagawa terranes. Other accreted material includes ophiolitic sequences, e.g. the Yakuno ophiolite of the Maizuru terrane, the Oeyama ophiolite of the Sangun terrane, and the Hayachine–Miyamori ophiolite of the South Kitakami terrane, and limestone‐capped ocean plateaus such as the Akiyoshi terrane. The ophiolitic units are likely derived from arc and back‐arc basin settings. There has been no continental collision in Japan, meaning the oceanic subduction record is more complete than in convergent orogens seen in intracontinental settings making this a good place to study the geological record of accretion. Hokkaido lacks most of the Paleozoic history recognized in Honshu, Shikoku, Kyushu, and the Ryukyu Islands to the south and its geology reflects the Cenozoic development of two convergent domains with volcanic arcs, their approach, and eventual collision. The Hidaka terrane reveals a cross section through a volcanic arc and the main accretionary complex of the convergent system is represented by the Sorachi–Yezo terrane.

Contribution of precipitation to groundwater flow systems in three major alluvial fans in Toyama Prefecture, Japan: stable-isotope characterization and application to the use of groundwater for urban heat exchangers - Nagisa Okakita; Kaname Iwatake; Hiromichi Hirata; Akira Ueda (Hydrogeology Journal, 2019)

Regulation of asymmetric polar auxin transport by PsPIN1 in endodermal tissues of etiolated Pisum sativum epicotyls: focus on immunohistochemical analyses - Motoshi Kamada; Kensuke Miyamoto; Mariko Oka; Junichi Ueda; Akira Higashibata (Journal of Plant Research, 2018)

Enrichment and characterization of a bacterial mixture capable of utilizing C-mannosyl tryptophan as a carbon source - Tanim J. Hossain; Shino Manabe; Yukishige Ito; Toshiya Iida; Saori Kosono; Kenji Ueda; Akira Hosomi; Daishi Inoue; Tadashi Suzuki (Glycoconjugate Journal, 2018)

Angiotensin II induces the aggregation of native and oxidized low-density lipoprotein - Akira Sato; Chiemi Ueda; Ryu Kimura; Chisato Kobayashi; Yoji Yamazaki; Keiichi Ebina (European Biophysics Journal, 2018)

Hydrogeochemistry and quality of surface water and groundwater in the vicinity of Lake Monoun, West Cameroon: approach from multivariate statistical analysis and stable isotopic characterization - Brice T. Kamtchueng; Wilson Y. Fantong; Mengnjo J. Wirmvem; Rosine E. Tiodjio; Alain F. Takounjou; Jules R. Ndam Ngoupayou; Minoru Kusakabe; Jing Zhang; Takeshi Ohba; Gregory Tanyileke; Joseph V. Hell; Akira Ueda (Environmental Monitoring and Assessment, 2016)

Genetic population structure of Crystallichthys matsushimae (Cottoidei: Liparidae) with comments on color variation - Akira Tohkairin; Yoshiaki Kai; Yuji Ueda; Tomonori Hamatsu; Masaki Ito; Tetsuji Nakabo (Ichthyological Research, 2016)

A Fluorescence-Labeled Heptapeptide, (FITC)KP6, as an Efficient Probe for the Specific Detection of Oxidized and Minimally Modified Low-Density Lipoprotein - Akira Sato; Chiemi Ueda; Ryu Kimura; Chisato Kobayashi; Yoji Yamazaki; Keiichi Ebina (Journal of Fluorescence, 2016)

Effect of habitat transformation from grassland to Acacia mangium plantation on dung beetle assemblage in East Kalimantan, Indonesia - Akira Ueda; Dhian Dwibadra; Woro A. Noerdjito; Sugiarto; Masahiro Kon; Teruo Ochi; Masayoshi Takahashi; Kenji Fukuyama (Journal of Insect Conservation, 2015)

Morphological divergence between two color morphotypes of Crystallichthys matsushimae (Cottoidei: Liparidae) - Akira Tohkairin; Yoshiaki Kai; Yuji Ueda; Tomonori Hamatsu; Masaki Ito; Tetsuji Nakabo (Ichthyological Research, 2015)

Investigation of severe water problem in urban areas of a developing country: the case of Dhaka, Bangladesh - Mst. Shamsun Nahar; Jing Zhang; Akira Ueda; Fujishiro Yoshihisa (Environmental Geochemistry and Health, 2014)

Comprehensive Gene Expression Analysis of Cerebral Cortices from Mature Rats After Neonatal Hypoxic–Ischemic Brain Injury - Toshio Kojima; Yuto Ueda; Akira Sato; Hiroshi Sameshima; Tsuyomu Ikenoue (Journal of Molecular Neuroscience, 2013)

Gene Network Analysis to Determine the Effects of Antioxidant Treatment in a Rat Model of Neonatal Hypoxic-Ischemic Encephalopathy - Toshio Kojima; Yuto Ueda; Naoki Adati; Aya Kitamoto; Akira Sato; Ming-Chih Huang; Jesmine Noor; Hiroshi Sameshima; Tsuyomu Ikenoue (Journal of Molecular Neuroscience, 2010)

Relationship between copper biosorption and microbial inhibition of hydroxyl radical formation in a copper(II)–hydrogen peroxide system - Akira Nakajima; Yuto Ueda (World Journal of Microbiology and Biotechnology, 2008)

Functional role for redox in the epileptogenesis: molecular regulation of glutamate in the hippocampus of FeCl3-induced limbic epilepsy model - Yuto Ueda; Taku Doi; Keiko Nagatomo; L. James Willmore; Akira Nakajima (Experimental Brain Research, 2007)

Anticipation of affective image modulates visual evoked magnetic fields (VEF) - Keiichi Onoda; Yasumasa Okamoto; Kazuhiro Shishida; Akira Hashizume; Kazutaka Ueda; Akiko Kinoshita; Hidehisa Yamashita; Shigeto Yamawaki (Experimental Brain Research, 2006)

Generation of lipid radicals in the hippocampus of neonatal rats after acute hypoxic-ischemic brain damage - Yuto Ueda; Jesmin I. Noor; Keiko Nagatomo; Taku Doi; Tomoaki Ikeda; Akira Nakajima; Tsuyomu Ikenoue (Experimental Brain Research, 2006)

Growth and survival rates of large-type sporophytes of Ecklonia cava transplanted to a growth environment with small-type sporophytes - Yukihiko Serisawa; Masakazu Aoki; Tetsu Hirata; Alecia Bellgrove; Akira Kurashima; Yasutaka Tsuchiya; Toshihiko Sato; Hajime Ueda; Yasutsugu Yokohama (Journal of Applied Phycology, 2003)

Mitochondrials complex I activity is reduced in latent adriamycin-induced cardiomyopathy of rat - Kiyotaka Ohkura; Jong-Dae Lee; Hiromasa Shimizu; Akira Nakano; Hiroyasu Uzui; Motosaburo Horikoshi; Yasuhisa Fujibayashi; Yoshiharu Yonekura; Takanori Ueda (Molecular and Cellular Biochemistry, 2003)

Glutamate excess and free radical formation during and following kainic acid-induced status epilepticus - Yuto Ueda; Hidekatsu Yokoyama; Akira Nakajima; Jun Tokumaru; Taku Doi; Yoshio Mitsuyama (Experimental Brain Research, 2002)

Characterization of the human nebulette gene: a polymorphism in an actin-binding motif is associated with nonfamilial idiopathic dilated cardiomyopathy - Takuro Arimura; Takeyuki Nakamura; Shitoshi Hiroi; Manatsu Satoh; Megumi Takahashi; Nobuhisa Ohbuchi; Kazuo Ueda; Tatsuhito Nouchi; Noriko Yamaguchi; Jun Akai; Akira Matsumori; Sigetake Sasayama; et al. (Human Genetics, 2000)